"Don't put all your eggs in one basket!": Visiting Mike Richardson at Photonic Insights. Issue 6 (3rd November 2021) - Pozo, Jose
Abstract: The technical director of EPIC, Jose Pozo, talks to Mike Richardson, managing director at Photonics Insights, an R&D company focused on developing low‐cost spectrographic solutions particularly for agricultural markets.